Prevalensi dan karakteristik obesitas pada anak di Sekolah Dasar Saraswati V Kota Denpasar tahun 2016 - Kadek Adi Suryamulyawan; I Made Arimbawa (Intisari Sains Medis, 2019)
Introduction: One of the problems of excess nutrients that occur in children and received special attention in the world of health is obesity. Obesity itself can be defined as the accumulation of excess fat raises the risk of health problems. The prevalence of obesity in children in the world between 1980 and 2013 increased by 47.1%. Childhood obesity has both immediate effects and long-term health. This study aims to determine the prevalence and characteristics of obesity in children at elementary school.Method: This research is a descriptive cross sectional study, conducted in Saraswati V Denpasar elementary school, November - December 2016, by taking samples of obese children in Saraswati V elementary school Denpasar 2016.Result: From the results, 17.2% children with obese, 18.2% children with overweight, 54.6% children with normal BMI, and 10.0% children with underweight from total students many as 1003 children. While the characteristics of obese children obtained: 62.2% of obese children aged <9 years, 73.4% of obese children of boy, 86.7% of obese children have birth weight â‰¥2500 gram, 62.9% do breakfast, 98,6% escorted to school, 67.8% had obese father and 34.3% had obese mothers, 99.3% had educated father and 97.2% had educated mother.Conclusion: The high prevalence of obesity, which is 17.2%, is a focus that should be of a better concern than parents, and the government.